Pengaruh Kepemimpinan Transformasional dan Lingkungan Kerja Non Fisik terhadap Kesejahteraan Psikologis Pegawai pada DPM-PTSP Provinsi Jambi - Aldi Aditya Firdaus; Zulfina Adriani; Dian Mala Fithriani Aira (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to analyze the influence of transformational leadership and non-physical work environment on the psychological well-being of employees at the Investment and Integrated Services Agency (DPMPTSP) of Jambi Province. The research method used is a quantitative method with a survey approach. The research population included all 106 employees of the DPMPTSP of Jambi Province, with a sample of 84 respondents determined using the Slovin formula. Data were collected through questionnaires designed based on indicators of transformational leadership, non-physical work environment, and psychological well-being. Data analysis was conducted using descriptive statistical tests to examine the relationships and influences between variables. The results of the study show that: (1) Transformational leadership is in the good category with an average score of 330.1; (2) The non-physical work environment is in the very conducive category with an average score of 357.3; (3) The psychological well-being of employees is in the prosperous category with an average score of 317.7. The partial test (t-test) results show that transformational leadership has a positive and significant effect on psychological well-being (p = 0.019 < 0.05). The non-physical work environment also has a positive and significant effect on psychological well-being (p = 0.000 < 0.05). The results of the simultaneous test (F-test) show that both independent variables together have a significant effect on well-being (p = 0,000 < 0,05) with a coefficient of determination (R²) of 0.618, which means that 61.8% of the variation in psychological well-being is explained by transformational leadership and the non-physical work environment.